Production Management of ADiTV Yogyakarta Special Dialogue (Dialog Khusus) Program Viewed from the Perspective of Islamic Management - Zain Ma'ruffatah; Nur Aini Shofiya Asy'ari (Sahafa Journal of Islamic Communication, 2018)
Media have a wide range and an important role for the community to make it easier in getting information. One of the media that has an important role in the delivery of information is the electronic media of Television that becomes the most effective tool of information delivery since the television conveys direct and quick information in the form of audio and visual. ADiTV Yogyakarta Station is one of the local stations in Yogyakarta. Special Dialogue (Dialog Khusus) program is an interactive talk show program of ADiTV that reviews some information about education, tourism, culture, economy in Yogyakarta and surrounding areas. This research aims to analyze the production management of ADiTV Yogyakarta special dialogue program in the perspective of Islamic management. The research method was descriptive qualitative. The data were collected from interviews, observation and documentation. The conclusion of this research was production management of special dialogue program was in conformity with the theory applied to production management stage of television program according to Fred Wibowo and it was related to management functions according to George R Terry and Dr. Sondang P Siagian. That theory was described in the Qur'an that management in the perspective of Islam is very important and needed by humans in conducting activities. It is expected that this research can provide a science study for management of an event program in the perspective of Islamic management. Keyword : Perspective of Islamic Management, Production Management, Dialog Khusus Program